Unconscious system-psychodynamics within a German 4IR engineering company in South Africa - Mayer, Claude-Hélène; Oosthuizen, Rudolf M. (Frontiers in Psychology, 2022)
This article focuses on systems psychodynamics and particularly on the CIBART-model which explores conflict, identity, boundary, authority, role and task and how these phenomena work out on an unconscious level. Therefore, this article presents empirical findings on CIBART in a German multinational engineering organization operating in South Africa. For this study, 16 managers where interviewed on their transformation towards Industry 4.0 with special interest in the interconnection how CIBART aspects play out in the South African context. Findings show that all of the CIBART-phenomena are important during the transformation to more advanced technological levels and restructuring processes. Conclusions are drawn and recommendations are given how to deal with systems-psychodynamic influences within the organization.